Chlorhexidine with or without alcohol against biofilm formation: efficacy, adverse events and taste preference - Gabriela Otero dos SANTOS; Fernanda Carpes MILANESI; Bruna Frizon GREGGIANIN; Marilene Issa FERNANDES; Rui Vicente OPPERMANN; Patricia WEIDLICH (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract In recent years, different chlorhexidine formulations have been tested, including an alcohol-free alternative, but the effect of this solution on early biofilm formation is not clear. A crossover, randomized, double-blind clinical trial was conducted to evaluate the effect of two chlorhexidine solutions against supra- and subgingival biofilm formation (NCT#02656251). Thirty-five participants were randomized and asked to rinse twice daily with 15 ml of an alcohol-containing 0.12% chlorhexidine solution, an alcohol-free 0.12% chlorhexidine solution, or placebo. The study was conducted in three experimental periods of 4 days each, with a 10-day washout between the periods. All the experimental periods followed the same protocol, except that the solutions were switched. Biofilm distribution was evaluated every 24 hours by the Plaque-Free Zone Index, during 96 hours. Adverse events were self-reported and sensory evaluation was performed using a hedonic scale. Compared to the placebo, the chlorhexidine solutions resulted in a significantly higher number of surfaces free of plaque over 96 hours (p < 0.01), and were able to prevent subgingival biofilm formation (p < 0.01). The alcohol-free chlorhexidine solution was associated with a lower incidence of adverse events, compared with alcohol-containing chlorhexidine (p < 0.05); it also received better sensory evaluation and acceptance by trial participants, compared with the alcohol-containing chlorhexidine (p = 0.007), and had a similar inhibitory effect on the formation of supra- and subgingival biofilms.